Evaluation of Astroskin Bio-monitor during high intensity physical activities - Villa-Colín, J.; Shaw, T.; Toscano, W.; Cowings, P. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2018)
As humans go deeper into space, the need for a compact and accurate health monitoring system is imperative for the Exploration Medical Capability (ExMC) Element of Human Research Program (HRP). Thus, it is necessary to develop new technologies and advances in support of long duration space missions. In the study conducted, the goal was to validate the second prototype of the Astroskin bio-monitor system performance, developed by Carré Technologies in collaboration with the Canadian Space Agency (CSA), during high intensity physical activities. The Astroskin system is designed as a garment with built-in sensors, a headband with an optical sensor and a module that connects to the garment; allowing monitoring, recording and analyzing physiological parameters such as the electrocardiogram (ECG), heart rate, blood pressure, pulse oximetry, respiratory rate, and body temperature in a non-obtrusive way. The results provided feedback for improvements both in hardware and software. A previous prototype was tested in an analog space environment HERA in 2016, monitoring a crew’s physiological parameters for 24-hour sessions.